The soulmate - Hepworth, Sally (New York : St. Martin's Press, 2023)
When her husband becomes a local hero, saving person after person from ending their lives until one night he doesn't, Pippa discovers he knew the victim and wonders if she jumped or was pushed? A question that cracks the foundations of the life they$1 (Bve built. s
"First published in 2023 in Australia by Pan Macmillan Australia Pty Ltd."--Title page verso.
Keywords: Betrayal -- Fiction; Cliffs -- Fiction; Marriage -- Fiction; Secrecy -- Fiction; Spouses -- Fiction; Suicide -- Prevention -- Fiction; Suicidal behavior -- Fiction; Portsea (Vic.) -- Fiction; Australia -- Fiction; Thrillers (Fiction); Domestic fiction